Clinical Outcome and Viral Genome Variability of Hepatitis B Virus–Induced Acute Liver Failure. Issue 3 (11th February 2019) - Anastasiou, Olympia E.; Widera, Marek; Westhaus, Sandra; Timmer, Lejla; Korth, Johannes; Gerken, Guido; Canbay, Ali; Todt, Daniel; Steinmann, Eike; Schwarz, Tatjana; Timm, Jörg; Verheyen, Jens; et al.
Abstract : Acute hepatitis B virus (HBV) infection remains a frequent cause of acute liver failure (ALF) worldwide. ALF occurs in 0.1%‐0.5% of infected patients. The aim of this study was to scrutinize the outcome of patients with HBV‐induced ALF and mutational patterns of HBV variants, which might contribute to ALF. From 2005 to 2016, 42 patients were treated for HBV‐induced ALF in the University Hospital Essen, Germany. Clinical and virological data from these patients were collected. As a control, 38 patients with acute hepatitis B (AHB) without liver failure were included. The HBV genome was sequenced by next‐generation sequencing (NGS). Mutations that were found by NGS were analyzed in vitro . Of 42 patients, 8 had ALF without spontaneous recovery (NSR): Seven patients underwent liver transplantation (LT) and one patient died before LT. Of 42 patients, 34 (81%) had spontaneous recovery (SR) and cleared the infection, achieving either anti‐HBs seroconversion or hepatitis B surface antigen (HBsAg) loss. HBV genotype (GT)‐D was the most frequent GT in patients with ALF. Mutations in HBV core, preS2, and small hepatitis B surface antigen (SHB) were more frequent in patients with ALF‐NSR compared with those with ALF‐SR or AHB. Amino acid deletions (del; 16‐22 and 20‐22) in preS2 and SHB mutation L49R were exclusively detected in patients with ALF‐NSR. In vitro analyses reveal that these mutations did not influence HBsAg secretion or infectivity. Conclusion: HBV GT‐D and increased variability in HBV core, preS2 region, and SHB are associated with a worse clinical outcome of acute HBV infection.